Teaching Kazakh language as a foreign language by the blended learning model - Nurzhanova, Aisulu; Baltagul Ospanova, Saltanat Beissembayeva,; Orazbekova, Zeine; Satbekova, Aigul (Opción, 2020)
This article describes the features of using the blended learning model when teaching the Kazakh language as a foreign language via comparative qualitative research methods. At a time when the system of information and communication technologies is updated every day, it becomes clear that it is necessary to change the form of training from traditional to a new format. In conclusion, the vitality of the Kazakh language is directly related to the completeness, novelty, and adaptability of its teaching methods to new realities.